1997
DOI: 10.1097/00004647-199701000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral [15O] Water Clearance in Humans Determined by Positron Emission Tomography: II. Vascular Responses to Vibrotactile Stimulation

Abstract: When used to measure blood flow, water leaves a residue in the vascular bed, which may contribute to the calculation of increased blood flow during functional activation of brain tissue. To assess the magnitude of this contribution with the two-compartment positron emission tomography (PET) method, we mapped the water clearance (K1) of the brain as an index of cerebral blood flow (CBF) and the apparent vascular distribution of nonextracted H2 15O (Vo). The latter map represented mainly the cerebral arterial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…This effect, called ''signal enhancement by extravascular protons'' (SEEP) [Stroman et al, 2002c[Stroman et al, , 2003b[Stroman et al, , 2005b, is thought to arise from a local change in fluid balance, which in turn may result from changes in perfusion pressure, production of extracellular fluid, neurons and glial cells swelling, and maintenance of ion and neurotransmitter concentrations at sites of neuronal activity [Fujita et al, 1997;Ohta et al, 1996;Stroman and Andrew, 2007;Stroman et al, 2002cStroman et al, , 2003bStroman et al, , 2005b. Previous studies showed that both the BOLD and the SEEP effects give a contribution to the signal change observed during spinal fMRI activity, with different relative proportions depending on field strength and TE value used [Stroman, 2005;Stroman et al, 2002c].…”
Section: Discussionmentioning
confidence: 99%
“…This effect, called ''signal enhancement by extravascular protons'' (SEEP) [Stroman et al, 2002c[Stroman et al, , 2003b[Stroman et al, , 2005b, is thought to arise from a local change in fluid balance, which in turn may result from changes in perfusion pressure, production of extracellular fluid, neurons and glial cells swelling, and maintenance of ion and neurotransmitter concentrations at sites of neuronal activity [Fujita et al, 1997;Ohta et al, 1996;Stroman and Andrew, 2007;Stroman et al, 2002cStroman et al, , 2003bStroman et al, , 2005b. Previous studies showed that both the BOLD and the SEEP effects give a contribution to the signal change observed during spinal fMRI activity, with different relative proportions depending on field strength and TE value used [Stroman, 2005;Stroman et al, 2002c].…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography (PET) studies using a radiolabeled water tracer have demonstrated that there is increased unidirectional clearance of water from the blood into the tissues at sites of neuronal activity in the brain. 17,18 Another factor influencing the local fluid balance is cellular swelling at sites of activity. Astrocytes make contact with both blood vessels and neurons and play a role in providing metabolites to neurons and in maintaining the extracellular concentration of glutamate.…”
Section: Proposed Physiological Origins Of Seepmentioning
confidence: 99%
“…[7][8][9] In addition, the increased blood flow to the active tissues has been shown to be accompanied by increased intravascular pressure, and increased production of extracellular fluid at sites of neuronal activity. 10,11 The net effect is a local increase in water content near active neural tissues which causes a higher MR signal intensity. Thus, spinal fMRI indirectly detects neuronal activity in spinal cord gray matter, and allows for mapping of spinal cord responses to sensory and motor stimulation.…”
Section: Introductionmentioning
confidence: 99%